Determinants of Life Insurance Purchase Intent Among Millennials - Isana Sri Christina Meranga (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
This study aims to investigate the factors influencing millennials' intentions to purchase life insurance. A conceptual framework was developed based on the Theory of Reasoned Action (TRA). Data was collected through electronic questionnaires from 270 sample of Indonesian millennials. The gathered data was analyzed using PLS-SEM 4. The findings reveal that attitude, subjective norms, personal values, motivation, and learning significantly influence millennials' intentions to purchase life insurance. A positive attitude, driven by perceived benefits and long-term financial security, emerged as a key determinant. Social influence, as reflected in subjective norms, also played a crucial role. Personal values, particularly those related to family security and financial stability, further reinforced the importance of life insurance. This research contributes to the literature by analyzing the factors influencing millennials' intention to purchase life insurance. By identifying key determinants like attitude, social norms, personal values, motivation, and learning, this study provides valuable insights for insurers to develop effective marketing strategies.